Jejunogastric Intussusception: A Case Report - Hussain, MM; Rahman, A; Abedin, MR; Habib, MA (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Jejunogastric intussusception is an established complication following any type of gastroenterostomy. In its acute form it presents with abdominal pain and lump suggestive of obstruction. It is also a rare cause of haematemesis. Chronic and intermittent presentation has also been described. It is a surgical emergency in its acute form. Early diagnosis and prompt treatment is required to avoid mortality. We report here a case that had a history suggestive of recurrent symptoms and ultimately presented as an acute emergency in the emergency department of Dhaka Medical College Hospital, Dhaka, Bangladesh DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11366 J Bangladesh Coll Phys Surg 2012; 30: 44-47